The Modernity of Middle English Manuscripts. A Multimodal Investigation - Anesa, Patrizia; Fornasini, Ilaria (Elephant & Castle, 2017)
This study investigates the interrelation between different semiotic resources in a corpus of sixty Middle English manuscripts dating from 1350 to 1500. The analysis focuses on two main forms of interaction between text and image, namely visual positioning and functionality, and their role in the transmission of meaning. In terms of visual positioning, three main macropatterns have been identified: separateness, inclusion, and integration. As regards functionality, the following patterns emerge: manifest functionality, co-functionality, and apparent unrelation. This study confirms that modern multimodal approaches to text analysis may be fruitfully employed to investigate Middle English manuscripts and their complex iconographic apparatus. Indeed, manuscripts do not represent merely an aesthetic juxtaposition of verses and pictures but a complex and interactive system based on the strategic and creative combination of different multimodal resources.